2010
DOI: 10.1021/jf903356m
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Depletion and Formation of α-Aminoadipic and γ-Glutamic Semialdehydes in Porcine Burger Patties with Added Phenolic-Rich Fruit Extracts

Abstract: The effect of added fruit extracts on the oxidation of muscle proteins in porcine burger patties subjected to cooking and chill storage was studied. Extracts from arbutus berries (Arbutus unedo L., AU), common hawthorns (Crataegus monogyna L., CM), dog roses (Rosa canina L., RC), and elm-leaf blackberries (Rubus ulmifolius Schott, RU) were prepared, characterized, added to burger patties (3% of total weight), and evaluated as inhibitors of protein oxidation. Negative (no added extract, C) and positive control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 38 publications
7
33
1
Order By: Relevance
“…Apparently, in this study lysine was more easily oxidized compared to proline and arginine, which was also found by Utrera et al (2011). Nevertheless, opposite results were published by Ganhão, Morcuende, and Estévez (2010b) and Armenteros, Heinonen, Ollilainen, Toldrá, and Estévez (2009) in which higher amounts of GGS and lower amounts of AAS were found in different meat products. The formation of both specific protein carbonyls from meat proteins involves the irreversible loss of essential amino acids and hence, the nutritional value of meat products (Estévez, 2011).…”
Section: Discussioncontrasting
confidence: 40%
“…Apparently, in this study lysine was more easily oxidized compared to proline and arginine, which was also found by Utrera et al (2011). Nevertheless, opposite results were published by Ganhão, Morcuende, and Estévez (2010b) and Armenteros, Heinonen, Ollilainen, Toldrá, and Estévez (2009) in which higher amounts of GGS and lower amounts of AAS were found in different meat products. The formation of both specific protein carbonyls from meat proteins involves the irreversible loss of essential amino acids and hence, the nutritional value of meat products (Estévez, 2011).…”
Section: Discussioncontrasting
confidence: 40%
“…initiation, propagation and termination, prevention of initiation by binding the substrate (ROS-the so--called reactive oxygen species) or neutralization of compounds accelerating the oxidation process (UV-Vis radiation, Unauthenticated Download Date | 5/10/18 6:05 PM transition metal ions, lipoxygenase), free radical scavenging, decomposition of the reactive products of lipid oxidation (hydroperoxides and non-radical substances) or the formation of the protective layer on the surface of the interface in multiphase systems [Brewer, 2011]. Some plant extracts containing phenolic compounds were reported to inhibit both lipid oxidation and deterioration of nutritional quality of meat proteins Ganhão et al, 2010b]. Phenolic compounds were suggested to act against oxidation-induced damage of myofi brillar protein by two mechanisms: metal chelation (leading to inactivation of nonheme iron prooxidant effect) and radical scavenging (they could be scavengers of iron-and lipid-mediated reactive oxidant species) [Estévez et al, 2008].…”
Section: The Use Of Antioxidant Additives In Reducing the Loss Of Thementioning
confidence: 99%
“…Litchi fl owers may be an effective natural antioxidant to reduce lipid and protein oxidation for frozen cooked meat products [Ding et al, 2015]. Ganhão et al [2010b] reported that using extracts from dog roses, common hawthorns, elmleaf blackberries, and arbutus berries during processing and storage of burger patties resulted in the inhibition of muscle protein oxidation. The application of fruit extracts as antioxidant and functional ingredients may increase the nutritional quality of the meat products.…”
Section: The Use Of Antioxidant Additives In Reducing the Loss Of Thementioning
confidence: 99%
“…Some ethanolic plant extracts contained phenolic compounds were also reported to inhibit both lipid oxidation and deterioration of nutritional quality of meat proteins [Hęś et al 2007, Ganhao et al 2010. Phenolic compounds were suggested to act against oxidationinduced damage of myofi brillar protein by two mechanisms: metal chelation (leading to inactivation of nonheme iron prooxidant effect) and radical scavenging (they could be scavengers of iron-and lipid-mediated reactive oxidant species) [Estevez et al 2008].…”
Section: Eff Ect On Nutritive Valuementioning
confidence: 99%